2021
DOI: 10.1016/j.eclinm.2021.100916
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems during COVID-19 pandemic and its’ association to psychological distress: A systematic review and meta-analysis

Abstract: Background: The emerging novel coronavirus disease 2019 has become one of the leading cause of deaths worldwide in 2020. The present systematic review and meta-analysis estimated the magnitude of sleep problems during the COVID-19 pandemic and its relationship with psychological distress. Methods: Five academic databases (Scopus, PubMed Central, ProQuest, ISI Web of Knowledge, and Embase) were searched. Observational studies including case-control studies and cross-sectional studies were included if relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
272
8
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 308 publications
(320 citation statements)
references
References 215 publications
(68 reference statements)
31
272
8
9
Order By: Relevance
“…1 A meta-analysis of 177 published studies revealed that insomnia symptoms were most prevalent in healthcare professionals (43%), which further indicated that age, gender, country and marital status did not impact prevalence rates. 71 As already mentioned, health professionals, especially frontline workers who regularly care for COVID-19 infected patients, may be at higher risk of insomnia, because of increased fear of risk of infection and death, as well as irregular and more frequent work schedules. [73][74][75] For other "essential" workers besides healthcare, earlier wake times, and reduced total sleep times were also seen, when compared to "non-essential" workers.…”
Section: Pragmatic Focus On Sequelae Of Insomnia and Hypersomniamentioning
confidence: 99%
“…1 A meta-analysis of 177 published studies revealed that insomnia symptoms were most prevalent in healthcare professionals (43%), which further indicated that age, gender, country and marital status did not impact prevalence rates. 71 As already mentioned, health professionals, especially frontline workers who regularly care for COVID-19 infected patients, may be at higher risk of insomnia, because of increased fear of risk of infection and death, as well as irregular and more frequent work schedules. [73][74][75] For other "essential" workers besides healthcare, earlier wake times, and reduced total sleep times were also seen, when compared to "non-essential" workers.…”
Section: Pragmatic Focus On Sequelae Of Insomnia and Hypersomniamentioning
confidence: 99%
“…The improvement in economic conditions and the release of public economic support in the form of unemployment insurance and stimulus checks may have been a factor in the recovery of mental health since April 2020. Studies show that sleep problems were common during the COVID-19 crisis and this was associated with depression among the general population [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, other investigations identified advanced age as a risk factor for sleep disturbances [16], being associated with a decline of sleep quality [17], especially in older individuals with depressive and anxiety symptoms [18]. A recent study also showed that older age represented a significant predictor of a higher association between sleep problems and psychological distress [19]. Moreover, social isolation could exacerbate feelings of loneliness which, in turn, could compromise sleep and psychological health among the older population [20,21].…”
Section: Introductionmentioning
confidence: 99%